A Global Call to Action on Antimicrobial Resistance at the UN General Assembly - Albert Figueras (Antibiotics)
As the United Nations General Assembly prepares to convene its second high-level meeting on antimicrobial resistance (AMR) in September 2024, it is crucial to reflect on the progress made since the first meeting in 2016 and the urgent need for immediate action [...]